Government-Leading Student Loan Schemes A Comparative Study of Hong Kong and Mainland China - Antonia Jiewei Lu; Derong Chen (Intelektual Pustaka Media Utama, 2014)
Having a careful examination of government-leading student loan schemes in China and Hong Kong, we can find a lot of differences and learn something from these two counterparts which are very typical country or area faced by challenges in financing higher education in the context of transition from elitism to mass higher education. This research attempts to make a comparison of government-leading student loan schemes between Hong Kong and China in the new century. Then emphasis is put on the principles or core values namely efficiency, equity and adequacy, and determining their implications presented in student loan schemes in these two counterparts. Finally, the paper arrives at some recommendations for improvements in them.